Life Outside: A Narrative Ethnographic Inquiry into the Determinants of Homelessness. Issue 3 (16th April 2019) - Graffy, Peter; McKinnon, Sara; Lee, Garrett; Remington, Patrick
ABSTRACT: Homelessness is one of the largest social issues currently in the United States.This study specifically investigates the lived experiences of those who are or were homeless in Madison, Wisconsin, to identify the uniquely pivotal aspects of their lives that led them down the path of homelessness. This study is based on participant observation and semistructured interviews with those who have personally experienced homelessness in Madison. The findings from this research suggest that the determinants of homelessness originate early in life and can manifest in a variety of ways throughout childhood and adulthood to ultimately culminate in becoming homeless.